2020
DOI: 10.3389/fnbeh.2020.00130
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomic Correlates of Distance and Direction Processing During Cognitive Map Retrieval

Abstract: Navigating toward a goal and mentally comparing distances and directions to landmarks are processes requiring reading information off the memorized representation of the environment, that is, the cognitive map. Brain structures in the medial temporal lobe, in particular, are known to be involved in the learning, storage, and retrieval of cognitive map information, which is generally assumed to be in allocentric form, whereby pure spatial relations (i.e., distance and direction) connect locations with each othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…The involvement of this region in the question-locked might reflect the recall process, since studies have demonstrated the parahippocampus to be implicated in mental imagery, recalling of a familiar area, and scene construction of imagined scenes in fMRI studies (Rosenbaum et al, 2004;Hassabis et al, 2007;Chrastil, 2013). The parahippocampus showing a higher TMA for the direction condition in the question-locked could reflect, as we expected, the retrieval process of landmarks, which is in line with a previous study in fMRI of the CMRT (Faulmann et al, 2020). Indeed, TMA was higher in the direction condition, probably because of the additional landmark.…”
Section: Brain Regions Involved In the Question-lockedsupporting
confidence: 91%
See 1 more Smart Citation
“…The involvement of this region in the question-locked might reflect the recall process, since studies have demonstrated the parahippocampus to be implicated in mental imagery, recalling of a familiar area, and scene construction of imagined scenes in fMRI studies (Rosenbaum et al, 2004;Hassabis et al, 2007;Chrastil, 2013). The parahippocampus showing a higher TMA for the direction condition in the question-locked could reflect, as we expected, the retrieval process of landmarks, which is in line with a previous study in fMRI of the CMRT (Faulmann et al, 2020). Indeed, TMA was higher in the direction condition, probably because of the additional landmark.…”
Section: Brain Regions Involved In the Question-lockedsupporting
confidence: 91%
“…No power analysis was performed. However, we aimed to recruit a number of participants similar to the study by Faulmann et al (2020), i.e., 23 participants. Participants were young and healthy (Mean = 23.13, SD = 3.18, from 18 to 31 years old) with no neurological disorders and came from all socioeconomic backgrounds.…”
Section: Participantsmentioning
confidence: 99%
“…The strongest activation peak in the brain was found in left Crus I during the encoding of shape and color combinations in a paired-associate learning task (Neuner et al 2007). Other spatial tasks that engage the cerebellum include mental rotation and mental transformation tasks (Bonda et al 1995;Parsons et al 1995;Vingerhoets et al 2002;Zacks et al 2002;Creem-Regehr et al 2007;Weiss et al 2009;Stoodley et al 2012;King et al 2019), mental navigation (Ino et al 2002;Faulmann et al 2020;Ramanoël et al 2020), and the judgment of orientation (Lee et al 2005). Mental rotation of letters activated cerebellar clusters in left lateral lobule VII/Crus I (Weiss et al 2009;Stoodley et al 2012).…”
Section: Spatial Processingmentioning
confidence: 99%
“…Therefore, different cerebellar clusters may be engaged for different component processes of a task, each of which is subserved by unique cerebro-cerebellar networks. This is exemplified by motor imagery, which has been shown to activate posterior cerebellar regions (e.g., Hanakawa et al 2008;Faulmann et al 2020) during both mental rotation and mental navigation tasks. This is discussed in more detail below (see Within-task topography).…”
Section: Spatial Processingmentioning
confidence: 99%